Introduction to the special issue on celebrating the 15th anniversary of JIOHS and the 70th anniversary of HUST - Luo, Qingming (Journal of innovative optical health sciences)
Since launching in 2008, Journal of Innovative Optical Health Sciences (JIOHS) has been published for 15 years until 2022. Supported by the founding advisor Prof. Britton Chance and other founding Editorial Members, JIOHS was quickly embraced by the biomedical optics community, especially in Asia. Authors submitted some of their high quality papers to JIOHS, which led to a constant Impact Factor (IF) increase from the ¯rst IF 0.632 to IF 2.396 (Journal Citation Report 2021). JIOHS is now one of the most important journals in the field of biomedical optics and biophotonics.